PENGARUH BUDAYA KERJA TERHADAP KINERJA GURU DAN PRESTASI BELAJAR SISWA SMA KABUPATEN SUMBA BARAT DAYA, NTT - Oktavianus Deke (Jurnal Edukasi Sumba (JES), 2017)
This study aims to find out: (1) the effect between biology teacher’s work culture and their teacher’s performances of senior high school (SHS); (2) the effect between biology teacher’s performances and student’s learning achievements of senior high school (SHS); and (3) the effect between biology teacher’s performances and student’s learning achievements through teacher’s performance of senior high school (SHS). The sample consisted of biology teachers teaching in Grades X and XI with a total of 20 teachers and students of Grades X and XI. The data were collected through questionnaires and tests. The data were analyzed by means of the path analysis technique. The results of the path analysis show that: (1) there is a significant effect between biology teacher’s work culture and their performances with p smaller than 0.05 and R2 of 33.1% and regression equation with Y = 36.316 + 0.652X; (2) there is a significant effect between biology teacher’s performances and student’s learning achievements with p smaller than 0.05 and R2 of 50.3% and regression equation with Y = 48.831 + 0.252Y; and (3) there is effect between biology teacher’s performances and student’s learning achievements through teacher’s performance with of t count 2.158  bigger than t table 2.093.